Refleksi Metafora Amanah pada Penyajian dan Pengungkapan Laporan Keuangan Baznas - Amalia, Baiq Naili (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aimed to determine how the application of PSAK 109 to the presentation and disclosure of financial statements reflected in the concept of trustworthy metaphor at BAZNAS East Lombok Regency. The development of the number of Muslim communities in Indonesia is very high but this is not in line with the potential of zakat recorded and collected at Baznas every year. The reason is the lack of trust of muzakki to channel their zakat funds to zakat management institutions. Thus, a good accounting system is needed to realize accountability and transparency in the presentation of financial statements in accordance with PSAK 109 standards. This research is a descriptive qualitative research with data collection techniques through interviews and observations for primary data, and literature studies for secondary data. The results of this study indicate that the application of zakat accounting with the reflection of the concept of trustworthy metaphor is good, seen from all forms of activities and preparation of financial statements carried out by holding the principles of shiddiq, amanah, tabligh, fathonah. In addition, the application of PSAK 109 related to the presentation and disclosure of financial statements is still not fully in accordance with applicable accounting standards.